The Role of Parents in Building the Character of Children in Rt 009 Rw 002 Rawasari Village - Ningsih, Putri Saptia; Nahuda (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
The inculcation of noble values and morals is indeed a highlight for every citizen. This is evidenced by the many complaints someone has about the behaviour of neighbours' children who are often labelled naughty and uncivilized. This label has become common due to the lack of education about children's activities and the focus of adults on what they are doing. Unknowingly what the neighbors said to the child was recorded and became a psychic stigma on him. And this is what makes it very difficult for some children to grow up with noble morals. Actions and perspectives in solving this problem are very diverse if we refer to what is understood by the community. Such diverse thoughts certainly become difficult to be used as a reference in solving problems. As a result, children's education and mentality cannot be resolved properly due to the lack of references for applicable solutions. This research uses a descriptive research method. This research method aims to describe, explain and answer the questions being studied in more detail by studying as many individuals, groups or events as possible. The purpose of this research is to encourage the role of parents in the formation of character in children who grow and develop in the surrounding environment so that children can carry out normal lives in general in the world of children.